Exploration of lead‐zinc deposits using electromagnetic method: A case study in Fengtai ore deposits in Western China. (17th February 2021) - Xue, Guoqiang; Zhou, Nannan; Wang, Ruiting; Liu, Hongtao; Guo, Wenbo
Abstract : The Fengtai Pb–Zn metallogenic deposits located in China's western region have good minerogenetic conditions and exploration potential. However, the Fengtai mining area passed through complex orogenic process zones, such as subduction, collision, and integration between the Yangtze Plate and the North China Plate. Existing geological research and drilling results showed that the ore bodies of large‐scale Pb–Zn deposits in the ore‐gathering area were steeply inclined, and the detection depths of the majority of the metal deposits were generally less than 300 m. Deep ore‐controlling structures at approximately 500–1, 000 m are not well understood. Therefore, high‐precision and large‐depth geophysical detection techniques are necessary to achieve the required accurate detection results. This study revealed that the resistivity values of the ore and host rocks were quite different, which is essential for effective and efficient geophysical prospecting. Based on the petrophysical result, the grounded‐wire transient electromagnetic method system has been found to be one of the better choices for the deep prospecting of the metal deposits and was applied to detect Pb–Zn deposits in the Bafangshan‐Erlihe area. First, the grounded‐wire transient electromagnetic method's effectiveness was verified using results from survey line 1 at a known ore deposit verified by the drilling result. Then, the technique was used to identify deposits in an unexplored area. A deep anticline and ore body were successfully imaged. Most lead‐zinc ore bodies are controlled by the hinge and two wings of the tight anticline, and distributed in the contact zone between limestone and phyllite. The results provide a critical basis for deep prospecting and drilling design. Abstract : The depth range of the conductive anomalies is about 500–800 m. Considering the volume effect of electromagnetic induction caused by the conductive target, the upper part of the conductive anomaly is inferred to be the ore bodies corresponding to the interface between the conductive and resistive layers. The SOTEM method has been verified to have deep detection capabilities in complex mountainous terrain.